Techniques and Methods for Toxic Agent Analysis and Removal - Nicoleta Sorina Nemeș; Petru Negrea (Toxics)
In order to protect the environment and public health, this Special Issue’s goal was to provide a platform for the discussion of emerging trends in the monitoring and removal of contaminants from soil, water, and air [...]